Advokasi Oleh Lembaga Adat Terhadap Korban Kekerasan Dalam Rumah Tangga Di Desa Tutuwaru Kecamatan Pulau Leti Kabupaten Maluku Barat Daya - Hadibah Zachra Wadjo; Stelvia Wemly Noya (PAMALI: Pattimura Magister Law Review, 2023)
Introduction: Settlement of cases in people's lives in Southwest Maluku Regency is mostly resolved through the Customary Courts or better known as the Customary Institutions. One of the problems that is always resolved in customary institutions is cases of domestic violence. The legal basis is the Criminal Code, Article 356 Apart from being regulated in the Criminal Code it is also regulated in Law no. 23 of 2014 concerning the Elimination of Domestic Violence.Purposes of the Research:  The aim of the research is to find out efforts to prevent criminal acts of domestic violence, overcome criminal acts of domestic violence, how do traditional institutions play a role in victims of domestic violence in the village of Tutuwaru.Methods of the Research: This type of research is normative empirical research, namely research with field data as the main data source, such as interviews and observations.Results of the Research: Research results show severe psychological suffering to someone. But by reconsidering what the risks are if her husband is in jail. So the victim chose to resolve cases of domestic violence through traditional channels. Completion according to custom or kinship which is usually carried out by the Tutuwaru village customary institution.